The use of two-dimensional NMR relaxometry in bread staling: a valuable tool?. (15th December 2017) - Curti, E.; Carini, E.; Cobo, M.F.; Bocher, T.; Vittadini, E.
Highlights: 1D and 2D 1 H NMR were used to investigate bread staling. 1D 1 H NMR indicated mono and multi exponential behaviours in T1 and T2 relaxation. 2D 1 H NMR indicated the presence of multiple T1 protons pools. 2D T1 –T2 maps were representative of physico-chemical changes during staling. Abstract: Staling of bread was investigated in terms of physico-chemical parameters and one (1D) and two dimensional (2D) 1 H Nuclear Magnetic Resonance (NMR) relaxometry. Physico-chemical properties were consistent with those generally reported for bread staling (crumb moisture loss, decrease in frozen water content, formation of amylopectin crystals, crumb hardening). One dimensional 1 H NMR investigation suggested the presence of only one T1 protons population, while T2 was representative of multiple proton populations, that well related to the observed physico-chemical changes. 1 H Two dimensional NMR provided an interesting insight of 1 H T1 dynamics, as it allowed to discriminate the contribution of five protons pools within the 1 H T1 relaxation.